The ecovillage as a regenerative peacebuilding agent: Tamera – healing biotope I and the “Global Campus” in the West Bank - Esteves, A. (P2P Foundation (blog), 2018)
This article explores the nature of the agency of ecovillages in regenerative peacebuilding through the analysis of the “Global Campus”, a program launched by the ecovillage of Tamera (Portugal), focusing on its activities in the West Bank. The analysis adds to existing theories on peacebuilding agents by arguing that, in such circumstances, the role of ecovillages is to diffuse the ecovillage model as a whole-system strategy of post-conflict reconstruction and promotion of sociocultural understanding and psychosocial stability among the parts formerly in conflict. It also argues that, when it is not possible to spatially reproduce the ecovillage model, due to recurring hostilities, political obstacles or cultural reasons, ecovillages can still act as agents of diffusion of technologies and strategies for working on issues of trauma, power, identity and historical memory between parts in conflict, as well as promoting energy autonomy and food security among those in disadvantaged positions.